Effects of traditional processing techniques on the nutritional and microbiological quality of four edible insect species used for food and feed in east Africa - Nyangena, D.N.; Mutungi, C.; Imathiu, S.; Kinyuru, J.; Affognon, Hippolyte D.; Ekesi, S.; Nakimbugwe, D.; Fiaboe, K.K. (MDPI, 2020)
Edible insects are increasingly being considered as food and feed ingredients because of their rich nutrient content. Already, edible insect farming has taken-off in Africa, but quality and safety concerns call for simple, actionable hazard control mechanisms. We examined the effects of traditional processing techniques—boiling, toasting, solar-drying, oven-drying, boiling + oven-drying, boiling + solar-drying, toasting + oven-drying, toasting + solar-drying—on the proximate composition and microbiological quality of adult Acheta domesticus and Ruspolia differens, the prepupae of Hermetia illucens and 5th instar larvae of Spodoptera littoralis. Boiling, toasting, and drying decreased the dry matter crude fat by 0.8–51% in the order: toasting > boiling > oven-drying > solar-drying, whereas the protein contents increased by 1.2–22% following the same order. Boiling and toasting decreased aerobic mesophilic bacterial populations, lowered Staphylococcus aureus, and eliminated the yeasts and moulds, Lac+ enteric bacteria, and Salmonella. Oven-drying alone marginally lowered bacterial populations as well as yeast and moulds, whereas solar-drying alone had no effect on these parameters. Oven-drying of the boiled or toasted products increased the aerobic mesophilic bacteria counts but the products remained negative on Lac+ enteric bacteria and Salmonella. Traditional processing improves microbial safety but alters the nutritional value. Species- and treatment-specific patterns exist.